The Impact of Learning Agility on Work Engagement is Mediated by Psychological Empowerment and Resilience in Millennial Workers - Didi Sutardi; Dewiana Novitasari (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Millennial workers have the characteristic of not feeling tied to their work and this can have an impact on the organizations/companies that employ them. This research aims to determine the magnitude of the influence that learning agility has on work engagement through the mediation of psychological empowerment and resilience. This research uses a quantitative causality design. The respondents were 100 millennial workers born between 1981 and 1996. Sampling was carried out using convenience sampling. Data collection was carried out via Google form which was distributed to the worker community via social media Facebook, Linkedin and Whatsapp. The results of this research found that learning agility has no direct effect on work engagement of millennial workers. Psychological empowerment and mediating resilience are some of the effects of learning agility on work engagement. This research contributes to efforts to increase work engagement in millennial generation workers through factors such as learning agility, psychological empowerment and resilience.